METHODOLOGICAL ASPECTS OF TEACHING INFORMATION AND COMMUNICATION TECHNOLOGY AT THE UNIVERSITIES - Dsprof. Lutfillaev MX; Djabbarov BB (European Journal of Humanities and Educational Advancements, 2023)
The article covers the issues of using information and communication and Internet technologies in improving educational processes and the concepts of researching the problem of education in formatting . In particular, the fact that information technologies allow to increase the activity of students, increase the professional level of the teacher and the level of interaction of the participants of the educational process, as well as the fact that the information and communication technologies tools used in modern education provides an opportunity to achieve high educational results. New technologies have been researched to ensure mutual cooperation between teacher and student in the open and distance education system